Possible dialogues between Logotherapy and Judaism (Research, Society and Development, 2021)
The work of Viktor Frankl is incessantly crossed by themes linked to human spirituality. Of course, much of this was due to the author's experience in the concentration camps of Nazi Germany, experienced as a Jew. Moreover, it is well known that Jewish religious practice would accompany the author until his last days. In this sense, this paper aims at analyzing possible common aspects between the Therapy of Viktor Frankl and Judaism, both in the religious and cultural character of the latter. This was done through a methodology of bibliographic review on the subject. In order to do so, biographical aspects of the author were investigated, as well as theoretical elements of Logotherapy linked more closely to the question of religiosity and spirituality, in order to familiarize the reader with the theme. Dialogue with Judaism was guided by important works of this religion, where correspondence was sought for the theoretical aspects of Logotherapy. Finally, there were several points of convergence, which could be better understood in future researches on the subject.